Genomic resequencing reveals genetic diversity, population structure, and core collection of durian germplasm - Yiwang Zhong; Liying Feng; Huidong Deng; Xiaohao Ji; Jing Zhang; Yangyang Sun; Peifan Lin; Yang Qiao; Shenghua Xie; Haibo Wang; Lijun Guo; Xuejie Feng (Communications Biology)
Abstract Durio zibethinus Murr. is a tropical fruit crop of growing global importance, prized for its unique flavor and nutritional value. Yet only a narrow genetic base has been utilized in breeding efforts. We performed whole-genome resequencing of 114 diverse durian accessions collected in China, identifying over 39 million high-quality SNPs across the genome, revealing genome-wide patterns of diversity. Population structure analysis revealed three major genetic clusters, supported by PCA, phylogenetic analysis, and STRUCTURE modeling. Genome-wide scans identified candidate selective sweeps, and several genes potentially under selection. From the 114 accessions, we further identified a core collection of representative durian germplasms capturing the majority of the species’ genetic diversity. This subset includes both elite cultivars and genetically distinct individuals. Our study provides insights into the genetic diversity and population structure of cultivated durian. The defined core collection and genomic variation map establish a valuable resource for durian breeding and germplasm conservation. These findings will facilitate the identification of superior alleles for important traits and guide future durian improvement programs.